Planning for the market: business planning before marketing and the continuation of organizing efforts - Shane, Scott; Delmar, Frédéric (Journal of Business Venturing, 2004)
Drawing on goal setting theory, we argue that writing business plans before undertaking marketing activities should enhance the continuation of venture-organizing efforts. We examine 223 new venture-organizing efforts initiated in the first 9 months of 1998 by a random sample of Swedish entrepreneurs and show that those organizing efforts in which entrepreneurs completed business plans before talking to customers and beginning marketing or promotion had a lower hazard of termination than other organizing efforts.